Transfusion‐related alloimmunization in children: epidemiology and effects of chemotherapy. Issue 3 (27th May 2016) - Solh, Z.; Athale, U.; Arnold, D. M.; Cook, R. J.; Foley, R.; Heddle, N. M.
Abstract : Background & Objectives: Alloimmunization rates following red blood cell (RBC) transfusion in paediatric oncology are not known. This study aimed to: (1) describe frequency and specificity of alloantibodies in paediatric oncology patients after RBC transfusions; (2) determine the effect of chemotherapy on alloimmunization rate. Materials & Methods: Retrospective cohort study of paediatric patients at a tertiary care hospital is evaluated by two groups: control group, paediatric patients without cancer; study group, paediatric oncology patients who received chemotherapy. Alloimmunization was defined as clinically significant IgG alloantibody formation against RBC antigens. Results: A total of 1273 children were evaluated including 324 in study group, 909 controls, and 40 haemoglobinopathy patients. Overall, frequency of alloimmunization was 1·5%: 0·3% (95% CI: 0, 1·90) in study group; 1·3% (95% CI: 0·73, 2·32) in control group and 15% in haemoglobinopathies. The association between chemotherapy and alloimmunization was not significant; P value = 0·20 Fisher's exact test, OR 0·23 (95% CI: 0·03, 1·79). Conclusion: This is the first study exploring RBC alloimmunization in paediatric patients by diagnosis. Alloimmunization frequency was low. It was not possible to determine an association between chemotherapy and alloimmunization due to the low event rate.